THE ANALYSIS OF HEATHCLIFF CHARACTER IN WUTHERING HEIGHTS BY EMILY BRONTE: A SIGMUND FREUD’S THEORY: THE ANALYSIS OF HEATHCLIFF CHARACTER IN WUTHERING HEIGHTS - zakrimal _ mamal (BASIS (Bahasa dan Sastra Inggris), 2017)
This thesis is to find out the id and ego of Heathcliff in Wuthering Heights by Emily Bronte, and qualitative methodology is applied in analysing the character of Heathcliff through Sigmund Freud approach. The writer collects the data through primary and secondary data and analyzing the data by using intrinsic and extrinsic approach, and in reporting, the writer applies a descriptive analysis. The result of this thesis found that Heathcliff is id personality which is rude, irrational, revenger, and disbelief in God. The last is this research is wished to be a useful, helpful and good reference to the literature students especially, and reading material to the readers generally to learn and obtain some good points behind the Wutherin Heights to leave us a better lives.